Analysis of the Risk Factors Associated With Obstructive Sleep Apnea Syndrome in Chinese Children - Xiao, Ling; Su, Shuping; Liang, Jia; Jiang, Ying; Shu, Yan; Ding, Ling (Frontiers in Pediatrics, 2022)
Objective The present study was developed to explore risk factors related to the incidence and severity of obstructive sleep apnea syndrome (OSAS) in children. Methods The present study enrolled pediatric patients who admitted to our department for snoring and/or open-mouth breathing. All children completed a questionnaire and underwent physical examination and polysomnography (PSG). The cases were separated into OSAS and primary snoring (PS) groups. Factors associated with these two groups were analyzed, with risk factors significantly associated with OSAS then being identified through logistic regression analyses. OSAS was further subdivided into mild, moderate, and severe subgroups, with correlations between risk factors and OSAS severity then being analyzed. Results In total, 1,550 children were included in the present study, of which 852 and 698 were enrolled in the OSAS and PS groups. In univariate analyses, obesity, family passive smoking, a family history of snoring, allergic rhinitis, asthma, adenoid hypertrophy, and tonsil hypertrophy were all related to pediatric OSAS (P < 0.05). In a multivariate logistic regression analysis, adenoid hypertrophy (OR:1.835, 95% CI: 1.482–2.271) and tonsil hypertrophy (OR:1.283, 95% CI:1.014–1.622) were independently associated with the risk of pediatric OSAS (P < 0.05). Stratification analyses revealed that OSAS incidence increased in a stepwise manner with increases in adenoid and tonsil grading (P < 0.01). Correlation analyses revealed that adenoid hypertrophy and tonsilar hypertrophy were not significantly associated with OSAS severity (r = 0.253, 0.069, respectively, P < 0.05), and tonsil and adenoid size were no correlation with obstructive apnea-hypopnea index (OAHI) (r = 0.237,0.193, respectively, P < 0.001). Conclusion Obesity, family passive smoking, a family history of snoring, allergic rhinitis, asthma, tonsil hypertrophy, and adenoid hypertrophy may be potential risk factors for pediatric OSAS. Adenoid hypertrophy and tonsil hypertrophy were independently related to the risk of pediatric OSAS, with OSAS incidence increasing with the size of the adenoid and tonsil, while the severity of OSAS is not parallel related to the adenoid or tonsil size.